Comparative study between biological and chemical agents for control sheath blight disease of rice - Monsur, Mohammad Abul; Biñas, Sharmaine C.; Herath, Shashika Neranjan; Ambita, Israel Dave V.; Tasnim, Zarin; Pangga, Ireneo B.; Cumagun, Christian Joseph R. (Journal of Plant Stress Physiology, 2023)
Biological control measures are indispensable to sustain global food security, due to it being economically profitable and environmentally sound. A comparative study was conducted to know the effectiveness of biological control measures compared with contact fungicide. Trichoderma spp. based bio fungicides Bioquick and Biospark were applied as preventive measures and contact fungicide as a curative measure for controlling sheath blight disease in rice varieties BR 71 and IR 24. Biospark and Bioquick were applied before disease development while, contact fungicide was used after the initiation of sheath blight disease. At the early stage of disease development, the effect of Bioquick, Biospark, and fungicide in terms of reducing percent relative lesion height and percent tiller infection are comparable. At 14 DAI and 18 DAI, contact fungicide performed best among the three control measures based on the two parameters. The genotypes of the rice accessions used in the study also appeared to be a factor in disease development, as evidenced by higher horizontal and vertical disease severity in BR71 than in IR24. Between comparison of Bioquick and Biospark in terms of reducing percent relative lesion height, percent tiller infection, and percent disease control, appeared to be higher in Biospark in both varieties. From this study, we can conclude that farmers can use Biospark as a biofungicide to get maximum benefit considering rice yield and ecology. However, its efficacy is slightly lower than chemical fungicides for controlling sheath blight disease of rice.